2018
DOI: 10.1371/journal.pone.0191010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of influenza virus replication by Wnt/β-catenin signaling

Abstract: Wnt/β-catenin signaling is an essential pathway in cell cycle control. Dysregulation of the Wnt/β-catenin signaling pathway during viral infection has been reported. In this study, we examined the effect of modulating Wnt/β-catenin signaling during influenza virus infection. The activation of the Wnt/β-catenin pathway by Wnt3a increased influenza virus mRNA and virus production in in vitro in mouse lung epithelial E10 cells and mRNA expresson of influenza virus genes in vivo in the lungs of mice infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…However, this virus also produces markedly less severe symptoms in paediatric than adult COVID-19 patients Su et al, 2020). Upregulated type I and II interferon-associated gene expression in children ( Figure 2B) might be indicative of more effective anti-viral immunity whereas higher Wnt pathway-associated gene expression in adults ( Figure 2B) might be relevant since Wnt activation has been shown to increase rates of influenza replication (More et al, 2018). To further assess epithelial-intrinsic factors that might explain the disparity in symptom severity, we compared the expression of a manually curated list of 99 genes associated with viral infection in epithelial cells (Table S2) in our laser-capture microdissected whole tracheobronchial epithelium dataset ( Figure 6A).…”
Section: Cultured Basal Cells Demonstrate Greater Age-related Transcrmentioning
confidence: 99%
“…However, this virus also produces markedly less severe symptoms in paediatric than adult COVID-19 patients Su et al, 2020). Upregulated type I and II interferon-associated gene expression in children ( Figure 2B) might be indicative of more effective anti-viral immunity whereas higher Wnt pathway-associated gene expression in adults ( Figure 2B) might be relevant since Wnt activation has been shown to increase rates of influenza replication (More et al, 2018). To further assess epithelial-intrinsic factors that might explain the disparity in symptom severity, we compared the expression of a manually curated list of 99 genes associated with viral infection in epithelial cells (Table S2) in our laser-capture microdissected whole tracheobronchial epithelium dataset ( Figure 6A).…”
Section: Cultured Basal Cells Demonstrate Greater Age-related Transcrmentioning
confidence: 99%
“…As influenza pathogenesis is determined in part by the host response, understanding the key host modulators of viral infection and virus-induced disease is a promising approach to host-oriented drug development for preventing the disease. The Wnt/β-catenin signalling pathway has been shown to play an important role in virus replication (More et al, 2018;Shapira et al, 2009) and virus-induced immune responses (Hillesheim, Nordhoff, Boergeling, Ludwig, & Wixler, 2014). Identification of miRNAs that interfere with IAV replication by modulating Wnt/β-catenin will provide new insights into the miRNA-Wnt/β-catenin signalling-IAV interaction network.…”
Section: Discussionmentioning
confidence: 99%
“…We then assessed whether the effects of miR-193b on IAV infection were dependent on the viral strain using an IAV luciferase reporter assay (More et al, 2018). The IAV luciferase reporter vector contains a firefly luciferase under control of NP 5′ and 3′ UTRs of influenza A/WSN/33, so it is able to respond to IAV.…”
Section: Further Characterisation Of the Anti-iav Activities Of Mirmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFβ signaling pathway was demonstrated to being a doubtful advantage in normal and pathogenic development, especially in organ fibrosis, vascular disorders, and carcinoma. Previous studies reported the dysregulation of the Wnt signaling pathway during pseudorabies virus (PRV) infection [24] and the enhanced influenza virus mRNA and virus production by triggering Wnt pathway [32]. The reaction to EBOV infection was regulated by TGFβ signaling pathway [33], and the improved secretion of TGF-β1 and vascular endothelial growth factor (VEGF) in EBOV-infected cells were improved by temporally upregulating TGF-β-modulated signaling responses.…”
Section: Discussionmentioning
confidence: 99%